Global Marketing Management - Kotabe Masaaki; Vavrus Frances (John Wiley And Sons, Inc, 2008)
Globalization Imperative, Ecomonic Enviroment, Financial Enviroment, Global Cultural Enviroment and Buying Behavior, Political and Legal Environments, Global Marketing Research, Global Segmentation and Positioning, Global Marketing Strategies, Global Market Entry Strategies, Golbal Sourcing Strategy, Global Product Policy Decisions I: Developing New Products for Global Markets, Global Product Policy Decisions II: Marketing Products and Sevices, Global Pricing, Communicating with the World Consumer, Sales Management, Global Logistics and Distribution, Export and Import Management, Planning and Organization and Control of Global Marketing Operations, Global Marketing and the Internet, Cases, Index.